Prevalence of Stunting among 10-Year Old Children in Indonesia - Taqwin Taqwin (Journal of Global Pharma Technology, 2020)
Children are characterized as healthy when they grow and develop adequately. This is determined through age-appropriate ideal height and weight measurements. This study aimed to quantify the prevalence of stunting among 10-year old children. This observational study had a cross-sectional design. This descriptive research was conducted from October to November 2019 using a total sample of 392 children obtained through the multistage proportional sampling to select participants from the student in 19 first elementary school in the study area. The anthropometric measurements of height were taken using a microtoice. The measurement results were compared with the World Health Organization (WHO) AntroPlus 2007 standards for 10-year old children. Height was measured using standard methods and height for age and the z-score was computed to assess stunting. The hypothesis test was done using ANOVA. The prevalence of stunting among 10-year old children in central Sulawesi, Indonesia is 24.7%. Poso's district has the highest percentage at around 35.9%, Donggala district is around 35.7%, Sigi district is around 16.5% and Palu City is around 12.5%. The highest mean for height was found in Palu City at 135,7 cm and the lowest was in Donggala district at 129,9cm. ANOVA showed a significant value of <0.001 with z-scores of -0.72, -1.63, -1.45 and -1.09 in Palu City, Donggala District, Poso and Sigi respectively. The prevalence of stunting in Central Sulawesi for children aged 10 years old is 24.7%. Donggala and Poso district have the highest prevalence of stunting. Some strategies need to be executed in order to improve the level of nutrition of elementary school children. This can be done by providing safe and hygienic school canteens, promoting healthy food diversity, encouraging more fish consumption and other healthy protein ingredients.Keywords: Children, South Sulawesi, stunting.